Extrafine triple therapy in patients with symptomatic COPD and history of one moderate exacerbation. Issue 5 (18th May 2019) - Singh, Dave; Fabbri, Leonardo M.; Corradi, Massimo; Georges, George; Guasconi, Alessandro; Vezzoli, Stefano; Petruzzelli, Stefano; Papi, Alberto
In chronic obstructive pulmonary disease (COPD), exacerbation history is the strongest predictor of future exacerbation risk [1, 2]. Large cohort studies have shown that patients with one exacerbation in the previous year have an approximately two-fold increased future exacerbation risk compared to patients with no exacerbations, the risk increasing to five-fold in those with two or more exacerbations [1, 2]. Most clinical trials of pharmacological treatments designed to prevent exacerbations have therefore used the inclusion criterion of at least one exacerbation in the previous year, with a minority requiring at least two exacerbations [3–6]. In patients with symptomatic COPD, severe/very severe airflow limitation, and a history of one moderate (and no severe) exacerbation, ICS-containing triple therapy significantly reduces exacerbation risk overall versus single or double maintenance therapy http://ow.ly/VgJC30o9pXC